STUDI BIOGEOGRAFIS IKAN PUYAU (osteochilus SP) BERBASIS PROFIL PROTEIN DARI DANAU ROWO IJO, SITUS BUKIT BANGKAI - Tanto Budi Susilo; Mochamad Arief Soendjoto; Oni Soesanto; Raifa Azizia Mustaqima; Rani Sasmita; Paola Bianchi (Bioscientiae, 2023)
This Bukit Bangkai would like be became a candidate for place evolution rock art heritage unit (PERAHU). In this site, the Rowo Ijo lake as a habitat, where it was found biogeographically, a Puyau fish (Osteochilus sp). Furthermore, the method of precipitation fraction of ammonium sulfate ((NH4)2SO4) with Lowry and SDS-PAGE elaboration was used, as the main method to obtain the protein profile of fish protein. Analysis of kinship relations was carried out using the UPGMA method based on the profile.. Based on the results of the fraction (NH4)2SO4 and Lowry methods, the optimum protein content was obtained, namely 68.93; 116.08; 6.72; 7.96 (mg/ml) in the 70-80% fraction and 4 samples from Banjar Regency 19.17; 16.93; 20.04; and 20.04 mg/mL in the 40-70% fraction, respectively. Based on the results of SDS-PAGE at the optimum level of protein; Puyau Rowo Ijo fish have 64 bands, with a profile of 11 bands on P.1R code, 9 bands on P.2R code, 10 bands on P.3R code and 9 bands on P.4R. For Puyau Banjar fish there are 25 bands with the following profile; each code P.1B and P.2B has 6 bands, while P.3B has 10 bands and P.4B has 3 bands. The types of proteins found were thought to include Actin Protein, Carbonic Anhydrase, Trypsin Inhibitor, -lactalbumin, and Lysozyme. The results of the UPGMA analysis based on the distribution of protein species and weights were that there was related closely to two groups form (clusters) between puyau from the Lake Rowo Ijo and Banjar Regency.